TINJAUAN YURIDIS TETANG PERJANJIAN KAWIN YANG DI BUAT SETELAH DILANGSUNGKANYA PERKAWINAN - Yongki Putra Thany (Universitas 17 Agustus 1945 Samarinda, 2014)
ABSTRACTMarriage agreement is an agreement between a husband and wife candidates to arrange a marriage due to their property in defiance of union assets. In the Article of Article 147 The Book of the Law and Article 29 of the Civil Law Act 1974 Nomor.1 About marriages arranged marriage covenant making legal actions conducted before or in the course of the marriageIn the Book of the Law and the Civil Law Act No. 1 of 1974 On Marriage is not regulated the manufacture of the Marriage Agreement after the marriage took place. Provisions in the law only regulates the Marriage Agreement made before or during the marriage took place.Married agreement must be made by notarial deed of marriage held article 147 the Code of Civil Law. While in article 29 of Law No. 1 of 1964 On Marriage, Marriage Agreement may be made by written agreement and authorized by the registration of marriage.